Prenatal Diagnosis of Fryns Syndrome: A Case Report - Miğraci Tosun; Handan Çelik; Emre Beşe; Erdal Malatyalıoğlu; Mehmet Çetinkaya; Mehmet Türe; Gönül Oğur (Medical Network, 2009)
Fryns syndrome (FS) is a rare malformation. Major diagnostic criteria include congenital diaphragmatic hernia, distal limb and nail hypoplasia and abnormal facial appearance. We report a case of FS referred to our clinic at 25 weeks' gestation with a diagnosis of congenital diaphragmatic hernia. Sonographic examination of the fetus revealed microretrognathia, a short neck with nuchal folds (17 mm), a left-sided diaphragmatic hernia, bilateral pelviectasis and cutaneous edema. The diagnosis of FS was made after exclusion of chromosome aberrations by amniocentesis and delivery of the fetus. Macroscopic inspection revealed low-set posteriorly rotated ears, microretrognathia, complet mid cleft palate, a broad nasal bridge, low hairline, short neck, distal limb hypoplasia, rocker bottom feet, atypical female dominant genitalia.